Film behaviour of vertical gas-liquid flow in a large diameter pipe - Zangana, Mohammed Haseeb Sedeeq (2011)
Gas-liquid flow commonly occurs in oil and gas production and processing system. Large diameter vertical pipes can reduce pressure drops and so minimize operating costs. However, there is a need for research on two-phase flow in large diameter pipes to provide confidence to designers of equipments such as deep water risers.